Imaging individual barium atoms in solid xenon by scanning of a focused laser for use in the nEXO experiment - Chambers, Christopher, author; Fairbank, William, advisor; Lee, Siu Au, committee member; Wilson, Robert J., committee member; Van Orden, Alan, committee member (Colorado State University. Libraries, 2019)
Neutrinoless double beta decay (0νββ) is a non-standard model decay process in which two simultaneous beta decays occur, with no emission of neutrinos. This decay is of great interest. If observed, it will demonstrate that the neutrino and anti-neutrino are not distinct. This decay also violates lepton number conservation, a requirement for some theories seeking to explain the matter-antimatter asymmetry of the universe. A measurement of the decay half-life will also give information on the absolute mass scale of the neutrinos. EXO-200 and nEXO use liquid xenon (LXe) time projection chambers (TPC) to search for 0νββ decay. EXO-200 first observed two neutrino double beta decay (2νββ) in xenon-136, the rarest decay ever observed. A low background measurement is vital to maximizing sensitivity to the 0νββ decay mode, yet to be observed. In this dissertation, research and development of a technique for positive identification of the barium-136 daughter (barium tagging) is presented. It is desirable to incorporate barium tagging into the future nEXO detector, as it provides discrimination against all background except for the 2νββ decay mode. The scheme being developed in this work involves extraction of the barium daughter in solid xenon with a cryogenic probe, followed by matrix-isolation fluorescence spectroscopy to tag the barium atom. This work focuses on the detection of individual barium atoms in a prepared solid xenon sample. Single atom sensitivity has been achieved, and a method for imaging of individual atoms by scanning of a focused laser has been demonstrated.